Analysis of a Stackelberg game between a customer and several cooperating suppliers: stability and efficiency. Issue 2 (2nd April 2016) - Ernez Gahbiche, Ibtissem; Hadjyoussef, Khaled; Jemai, Zied; Dogui, Abdelwaheb
ABSTRACT: We analyse the performances of a supply chain where multiple capacitated suppliers are solicited by a customer who offers a new product procurement suggestion. The customer allocates demand volume to suppliers in a way to maximise his own profit. On the other hand, suppliers can cooperate by forming coalitions. We study coalition structures' stability and show that such cooperation improves the total supply chain performances. We show however that decentralisation of decisions may lead to the loss of the offer even when suppliers cooperate. We show also that total performances can be more improved if suppliers and the customer cooperate together.